The dark heart of Italy - Jones, Tobias (London : Faber and Faber, 2007)
Why is Italy still riven with internal conflict? Tobias Jones set out to answer this and many other questions during his three-year voyage across the Italian peninsula. He discovers a country which is proudly visual rather than verbal and where crime is hardly ever followed by punishment.
Includes bibliographical references (pages 289-292) and index.
Keywords: Political corruption -- Italy; Italy -- Description and travel